A Study on the Impact of Leachate and Gaseous Contaminants Migration Towards the Human Health and Ecosystem: A Case Study of Nigeria - O.O, Ajani; G.O, Olutona; A.A, Adeniji; O.O, Jegede; T, Kolawole; E.N, Bassey (Research Advances in Environment, Geography and Earth Science Vol. 1, 2024)
Solid waste disposal by open dumpsite system pose a big source of health hazards especially in developing Nations such as Nigeria, the largest and the most populated in West Africa. The associated leachate migration problems constitute enormously to both environmental and health risks to the populace in and around these landfills. Geophysical and Geochemical investigations were carried out on the possible contamination effect of leachate migration on the groundwater, surface water and air environment on and around selected landfills. Results obtained show a high presence of Volatile Organic Compounds (VOC), Particulate matter (PM10), airborne dust, and traces of heavy metals both in surface-water and also groundwater, all from the selected landfills in Nigeria. Consequently, the geophysical investigation carried out on some of these landfills revealed high possibilities of leachate contamination in the groundwater due to relatively poor and or weak groundwater protective potential, and in most developing Nations, groundwater serves as the most reliable source of potable water for human consumption. Hence, the case study reveals a serious concern on the present state and management of open dumpsites in Nigeria.